A combination of five short tandem repeats of chromosome 15 significantly improves the identification of Prader-Willi syndrome etiology in the Argentinean population - Araoz, Hilda Veronica (2006)
Prader-Willi syndrome (PWS) is a multisystemic disorder caused by the loss of expression of paternally transcribed genes in the PWS critical region of chromosome 15. Various molecular mechanisms are known to lead to PWS: deletion 15q11-q13 (75% of cases), maternal uniparental disomy (matUPD15) (23%) and imprinting defects (2%). FISH and microsatellite analysis are required to establish the molecular etiology, which is essential for appropriate genetic counseling and care management. We characterized an Argentinean population, using five microsatellite markers (D15S1035, D15S11, D15S113, GABRB3, D15S211) chosen to develop an appropriate cost-effective method to establish the parental origin of chromosome 15 in nondeleted PWS patients. The range of heterozygosity for these five microsatellites was 0.59 to 0.94. The average heterozygosity obtained for joint loci was 0.81. The parental origin of chromosome 15 was established by microsatellite analysis in 19 of 21 non-deleted PWS children. We also examined the origin of the matUPD15; as expected, most of disomies were due to a maternal meiosis I error. The molecular characterization of this set of five microsatellites with high heterozygosity and polymorphism information content improves the diagnostic algorithm of Argentinean PWS children, contributing significantly to adequate genetic counseling of such families.